2017
DOI: 10.1021/acscatal.7b01400
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity-Tailored, Metal-Free Hydrolytic Dynamic Kinetic Resolution of Morita–Baylis–Hillman Acetates Using an Engineered Lipase–Organic Base Cocatalyst

Abstract: Metal-free enantiocomplementary hydrolytic dynamic kinetic resolution of Morita−Baylis−Hillman (MBH) acetates was developed using triethylamine (TEA) as a racemization catalyst and wild-type or engineered lipase B from Candida antarctica (CALB) as stereoselectivity-determining catalyst, leading to chiral MBH alcohols with tailor-made R or S configurations on an optional basis. In the TEA-WT CALB catalysis system, WT CALB displays excellent S enantioselectivity for a series of MBH acetates tested (up to 96% ee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…Nowadays, benefitting from the great development of biotechnology and green chemistry, a variety of synthetic strategies to β-hydroxy nitriles have been developed using purified enzymes or whole cell catalysts. Among them, lipases, 2,22,23 reductases, 1,[24][25][26] dehydrogenases, 27 and nitrilases 28,29 have been mostly employed toward the synthesis of chiral β-hydroxy nitrile via the kinetic resolution of racemic hydroxyl nitriles or the asymmetric reduction of β-oxo-nitriles. In addition, few publications have reported the use of monooxygenase for the asymmetric hydroxylation of 3-phenylpropanenitrile 30 or multi-enzymatic biosynthesis system of alcohol dehydrogenase/halohydrin dehalogenase treating on α-halo ketones and cyanide 31 to form this family of chiral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, benefitting from the great development of biotechnology and green chemistry, a variety of synthetic strategies to β-hydroxy nitriles have been developed using purified enzymes or whole cell catalysts. Among them, lipases, 2,22,23 reductases, 1,[24][25][26] dehydrogenases, 27 and nitrilases 28,29 have been mostly employed toward the synthesis of chiral β-hydroxy nitrile via the kinetic resolution of racemic hydroxyl nitriles or the asymmetric reduction of β-oxo-nitriles. In addition, few publications have reported the use of monooxygenase for the asymmetric hydroxylation of 3-phenylpropanenitrile 30 or multi-enzymatic biosynthesis system of alcohol dehydrogenase/halohydrin dehalogenase treating on α-halo ketones and cyanide 31 to form this family of chiral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al recently demonstrated that the natural (S)-preference of CALÀ B for these substrates could be altered to (R) through point mutations. [85] The key mutation leading to a modification in the enzyme enantiopreference was W104V (from tryptophan to valine), with A281L and A282K acting in concert to improve enantioselectivity. In addition, the introduction of triethylamine to the reaction mixture allowed them to transform the EKR into a dynamic kinetic resolution (Scheme 20).…”
Section: Chembiochemmentioning
confidence: 99%
“…Xia et al. recently demonstrated that the natural ( S )‐preference of CAL−B for these substrates could be altered to ( R ) through point mutations [85] . The key mutation leading to a modification in the enzyme enantiopreference was W104V (from tryptophan to valine), with A281L and A282K acting in concert to improve enantioselectivity.…”
Section: Enantioselective Biocatalytic Reactions For Preparation Of E...mentioning
confidence: 99%
“…The dynamic kinetic resolution of alcohols using metal‐based racemization catalysts in combination with lipases is well reported and there have been several reviews on the use of complexes of metals such as iron, ruthenium, and iridium. [77b], [77c], [77d], [77e], Acids and bases, zeolite, even light activated catalysts have also been used as racemization catalysts for the dynamic kinetic resolution of alcohols …”
Section: Dynamic Kinetic Resolution and Combining Chemo‐ And Biocamentioning
confidence: 99%